Overview of Protein Energy Intake and Infectious Diseases of Stunting Toddlers in Klitik Village, Geneng District, Ngawi Regency - Alifa Mariyatul Khiftiyah; Inne Soesanti; Mujayanto; Ani Intiyati (Journal of Nutrition Explorations, 2025)
Background stunting is still a serious problem in Indonesia, including in Klitik Village, Geneng District, Ngawi Regency, with a fairly high prevalence rate. Purpose This study aims to determine the description of energy intake, protein and infectious diseases of stunted toddlers in Klitik village, Geneng district, Ngawi regency. Method: This study is a descriptive study with 28 stunted toddlers as a sample. Energy and protein intake data were obtained through 24-hour recall, and infectious disease data through interviews using questionnaires; The analysis was carried out univariate and bivariate (cross table).  Result The results showed that the majority of the stunted toddlers in Klitik Village are male and are in the age group of 48–59 months. As many as 67.8% of toddlers have less energy intake and 64.3% have less protein intake. Most also had a history of infectious diseases (60.8%), including diarrhea (82.1%) and ISPA (67.9%). Bivariate analysis showed a tendency that toddlers with less energy and protein intake developed infectious diseases, which can worsen stunting conditions. Conclusion Therefore, nutritional interventions accompanied by efforts to prevent and handle infectious diseases need to be the focus in overcoming stunting in the region.